MEASURING THE COMMUNITY IN ONLINE CLASSES - Beth Rubin (Online Learning, 2013)
The paper addresses individual and group level phenomena in online classes, and proposes both theoretical and empirical approaches to examining them, following the example of organizational climate. It applies the concepts to the Community of Inquiry (CoI) model and develops a theory of composition for teaching presence, social presence and cognitive presence that relates isomorphic constructs at the individual and the class levels. Hypotheses are made about the agreement among students on survey questions that are used to measure individual perceptions of the three presences of the CoI, and tested through a set of statistics designed to measure the extent to which shared perceptions of these presences exist within classes.